The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/aepp.13104
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Digital Divide in the COVID‐19 Era

Abstract: The digital divide limits opportunities for those without ready access to Internet. Movement online of essential activities during COVID‐19 took inadequate Internet service from inconvenient to emergency/crisis for many households. A negative correlation between rurality and Internet speed was found at the county level, highlighting the struggle for rural areas. Schools tackle challenges of providing equitable educational access by attempting to provide access for students, while even households with service a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
196
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(211 citation statements)
references
References 10 publications
9
196
1
5
Order By: Relevance
“…Further examples can be seen, without resulting in a review, in relation to new directions of digital health that are significantly increased at the moment, such as teleophthalmology [ 25 ] or totally new ones such as digital contact tracing [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further examples can be seen, without resulting in a review, in relation to new directions of digital health that are significantly increased at the moment, such as teleophthalmology [ 25 ] or totally new ones such as digital contact tracing [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this has not always happened in a uniform way. The digital divide was a cause of this [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Covid-19 pandemic has hit every corner of the planet; however, the access to these technological solutions has not always been and still is not uniform due to the phenomenon called digital divide which depends on multifaceted aspects ranging from the lack of access to instrumental and network resources, to cultural and social barriers [ 10 , 11 ] and also to possible forms of communication disability.…”
Section: The Covid-19: a Pandemic Exploded During The Mobile Technmentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely the result of more students living on or near campus with better access to reliable and fast internet connections. Many students of agronomy, soils, and environmental science come from rural areas (McCallister et al, 2005;Miller, 2011) where access to reliable and fast internet connections is often a concern (Lai & Widmar, 2020). Aristovnik et al (2020) and Mardis (2013) also reported that students from rural areas globally had problems with access to reliable internet during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%